In Silico Estimation of Skin Concentration of Dermally Metabolized Chemicals - Tomomi Hatanaka; Saki Yamamoto; Mayuko Kamei; Wesam R Kadhum; Hiroaki Todo; Kenji Sugibayashi (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2017)
Background: A great deal of in silico estimation methods were proposed for skin concentration and permeation of drugs by many researchers including us. The aim of the present study was to expand our in silico estimation method of skin concentration to dermally metabolized chemicals.  Materials and Methods: A three-layered diffusion model consisting of stratum corneum, viable epidermis and dermis was constructed based on Fick's second law of diffusion incorporated with Michaelis-Menten equation and plasma clearance in the viable epidermis and dermis, respectively. Ethyl nicotinate was used as a model chemical, and the in vivo skin concentration of the ester and its metabolite, nicotinic acid were measured after topical application to hairless rats. Permeation parameters were determined from the in vitro permeation data through full-thickness skin and stripped skin after application of the ester or acid with and without esterase inhibitor treatment. Metabolic parameters were obtained from the metabolic profile of the ester using skin homogenate.  Results and Conclusion: The skin concentrations calculated from our improved model using the permeation and metabolic parameters obtained beforehand were similar to the observed values. Influence of cutaneous enzyme distribution and plasma clearance on the skin concentrations were also estimated using appropriately modified models, resulting in higher influence on the acid than the ester. This estimation method will become an effective tool to assess the efficacy and safety of dermally metabolized chemicals.